Identification of 12 novel mutations and two new polymorphisms in the arylsulfatase A gene: Haplotype and genotype-phenotype correlation studies in spanish metachromatic leukodystrophy patients - Gort, Laura; Coll, M. Josep; Chabás, Amparo (Human mutation, 1999)
Arylsulfatase A (ARSA) deficiency is the main cause of metachromatic leukodystrophy (MLD), a lysosomal disorder with no specific treatment. In view of the importance of genetic counseling, analyses of mutations and polymorphisms, including the ARSA pseudodeficiency allele, were carried out in 18 unrelated Spanish MLD patients. A systematic search allowed us to identify 100% of the alleles involving 17 different mutations, 12 of which are novel: G32S, L68P, R84W, P94A, G99V, P136S, W193X, H227Y, R288H, G308D, T327I, and IVS6‐12C→G. Two new polymorphisms, 2033C>T and 2059C>T, were identified in intron 6 which, in combination with two polymorphisms previously described (2161C>G and 2213C>G), gave rise to four different haplotypes in the control population. In addition, we also studied polymorphism 842G>T. Linkage disequilibrium was detected between mutations IVS2+1G→A, D255H, and T327I and specific haplotypes, suggesting a unique origin for these mutations. Moreover, mutation T327I was always associated with the T allele of the new rare variant A210A (893C>T). The distribution of mutation D255H (frequency 19.4%) among patients with different MLD clinical presentation revealed a clear genotype–phenotype correlation paralleling that reported for mutation IVS2+1G→A (frequency 25%). Among the novel mutations, only P136S and R288H occurred on a background of the ARSA pseudodeficiency allele. Screening 182 normal chromosomes identified a frequency of 8.8% of this allele; moreover, we identified two unrelated subjects with the polyA‐ mutation in the absence of the N350S mutation, and this infrequent haplotype reinforced the heterogeneity of conditions with ARSA deficiency. Hum Mutat 14:240–248, 1999. © 1999 Wiley‐Liss, Inc.